Viabilty Test of Fish Scale Collagen (Oshpronemus Gouramy) on Bone Marrow Mesenchymal Stem Cell Culture - Nur Azizah Hadi Azizah (Journal of Stem Cell Research and Tissue Engineering, 2022)
The role of type I collagen is as a matrix of extracellular proteins with characteristics of increased cell proliferation which directly affects the physiology and morphology of cells. Type 1 collagen can be obtained either from fish scales. This is what underlies the author to support engineering tissue used for the treatment of periodontal disease in the regenerative field by utilizing collagen derived from gouramy scales. As an initial step, the researchers wanted to conduct a study using collagen extract derived from gouramy scales (Osphoronemus gouramy) which was applied to bone marrow mesenchymal stem cell cultures to see viability in vitro. To determine the viability of collagen in carp (Osphronemus goramy) scales to bone marrow mesenchymal stem cells. Bone marrow mesenchymal stem cells are taken from mice and planted in 96 well plates. Collagen extracted from gouramy scales using the enzymatic method was dissolved in a condition medium and hydrolyzed into a collagen hydrolysis solution with each concentration of 0.01 mg / ml, 0.02 mg / ml, 0.04 mg / ml, 0.16 mg / ml, 0.32 mg / ml was put into the well prepared and incubated for 24 hours for the MTT assay. Collagen in carp scales can increase the viability of bone marrow mesenchymal stem cells with a percentage above 50% and the highest viability concentration at 0,01 mg / ml. The collagen of gouramy scales soaked in a medium condition has better viability than the collagen hydrolysis solution of carp. Collagen in carp scales is viable against bone marrow mesenchymal stem cells. Collagen scales of gouramy soaked in medium had the highest viability with an optimum dose of 0.01 mg / ml.